Induction, subculture cycle and regeneration of callus in Safed musli (Chlorophytum borivilianum) using different types of phytohormones - Nakasha, Jaafar Juju; Sinniah, Uma Rani; Kemat, Nurashikin; Mallappa, Kumara Swamy (Medknow Publications, 2016)
Background: Chlorophytum borivilianum is an industrially valued medicinal crop. Propagation through seeds is not feasible because of low germination percentage and long dormancy period. Therefore, callus culture and plant regeneration can be an alternative to improve this crop production. Also, callus can serve as an alternative source of bioactive compounds. Objective: To evaluate the effect of different phytohormones on callus induction, subculture cycle, and regeneration studies of callus in C. borivilianum. Materials and Methods: Young shoot buds of C. borivilianum were inoculated on Murashige and Skoog medium fortified with 3% sucrose and different concentrations (0, 1, 5, 10, and 15 mg/L) of either naphthalene acetic acid or 2,4-dichlorophenoxyacetic acid or indole-3-acetic acid and callus induction was evaluated up to four subcultures cycles. Shoot regeneration from callus was studied on Murashige and Skoog media fortified with 6-benzylaminopurine andkinetin or thidiazuron at varied levels (0, 0.5, 1, 2, and 3 mg/L). Microshoots were rooted on Murashige and Skoog media supplemented with 1.0 mg/L indole-3-butyric acid and plantlets were acclimatized before transferred to the natural conditions. Results: Callus induction was better evidenced on Murashige and Skoog media containing 5 mg/L 2,4-dichlorophenoxyacetic acid up to fourth subculture. Callus differentiated into shoots on Murashige and Skoog media fortified with 6-benzylaminopurine or kinetin, whereas thidiazuron completely failed to regenerate shoots. Furthermore, microshoots rooted on 1.0 mg/L indole-3-butyric acid containing Murashige and Skoog media. The rooted plantlets were successfully acclimatized and established in soil with 88.3% survivability. Conclusion: The type of auxins played an important role in inducing callus tissue from shoot bud explants of Safed musli. In future, this in vitro protocol could benefit in crop improvement programs and serve as a new source of bioactive compounds from Safed musli callus tissue for various therapeutic applications.